Osteoporosis in the orthopaedic practice - Synder, Marek; Bara, Tomasz (Menopause Review/Przegląd Menopauzalny, 2003)
Osteoporosis is diagnosed in 10% of whole human population in the world and in about 30% of women at the age over 50 years. Problem of osteoporosis cause the other problem of osteoporotic fractures. Most common osteoporotic fracture are proximal femur fractures, spine fractures as well as distal radius fracture. Most common and most dangerous osteoporotic fracture are the fracture around the hip. This type of fracture leads to social as well as to the treatment problems. Most of patients suffered from the hip fracture have other diseases which could complicate the treatment of the fracture. It is strongly recommended to treat surgically all hip fracture at the day of injury followed by early mobilization and individual PT program as soon as possible after the surgery. Other common osteoporotic fracture is spine fracture. There are mostly compressive vertebral fractures and very rare required surgical intervention. The distal radius fracture are also one of the frequent osteoporotic fracture. In a weak osteoporotic bone, the surgical treatment is sometimes indicated, but most of this type of fracture could be successfully treated by cast immobilization. The treatment of osteoporotic fracture must be performed together with a treatment of osteoporosis as a disease. Bisphosphonians, calcitonin and calcium are the method of treatment of osteoporosis together with treatment of the bone fractures.